Effect of selenium supplementation on polyunsaturated fatty acids in rat - Crespo, A.M.V. (2011)
The purpose of this work was to study plasma, adipose tissue, and liver fatty acids percentages of Wistar rats that drank water supplemented with several levels of sodium selenite for 1, 3, and 6 mo. In a general way, percentages of saturated, monounsaturated, and polyunsaturated fatty acids of supplemented groups were not different from those obtained with nontreated animals in the analyzed tissues. However, in rats supplemented with 0.5 ppm Se, mainly in adipose tissue, a polyunsaturated fatty acids increase (p<0.005) was observed for all times of treatment. This could suggest that 0.5 ppm Se supplement probably exercises a protective role on polyunsaturated fatty acids in that tissue. Supplements of 6.0, 15.0, and 54.0 ppm Se did not change unsaturation levels of fatty acids in the analyzed tissues.